Tathwir Wasilah Ta'lim al-Lughah al-Arabiyyah al-Tafa'uliyyah 'ala Asas al-Lu'bah al-Ta'limiyyah Quizizz fi Madah al-Mubtada' wa al-Khabar li Tullab al-Saff al-'Ashir bi al-Madrasah al-'Aliyah al-Hukumiyyah Palopo - Syamsuddin, Naidin; Kamal, Helmi (Institut Agama Islam Negeri (IAIN) Palopo, 2024)
AbstractThis research aims to determine the development process and validity level of the developed product. The type of research is research and development (R&D) using the D4 development model which consists of four stages, namely the identification, design, development, and dissemination stages. The research subjects are tenth graders at Walewang State High School. The data collection methods used are observation, interviews, validation sheets, student response questionnaires, and documents. The data were analyzed using qualitative and quantitative data analysis methods. The result of this research and development is an interactive Arabic language learning medium based on the Quizizz educational game for the subject-predicate material for tenth graders at Walewang State High School. Product validation results: 1) Subject matter expert validation obtained a score of 90.91%; 2) and media experts got 96.92%; 3) and language experts got 82.86%; 4) and education experts got 97.65%. Based on the results, it can be concluded that the developed learning media is very valid for application in Arabic language learning. Keywords: Interactive learning media, Quizizz educational game, subject-predicate???????? ??? ????? ??? ????? ????? ??????? ?????? ?????? ?????? ??????. ??? ????? ?? ????? ???????? (R&D) ???????? ????? ????? D4 ???? ????? ?? ???? ????? ??? ????? ???????? ????????? ????????? ?????????. ????? ????? ?? ???? ???? ?????? ???????? ??????? ???????? ??????. ??????? ??? ???????? ????????? ?? ???????? ????????? ?????? ?????? ?? ????? ????????? ??????? ?????? ????????. ??? ????? ???????? ???????? ?????? ????? ???????? ??????? ???????. ????? ??? ????? ???????? ?? ????? ????? ????? ??????? ????????? ??? ???? ?????? ????????? ?????? ?? ???? ??????? ?????? ????? ???? ?????? ???????? ??????? ???????? ??????. ????? ?????? ?? ??? ??????:1) ?????? ?? ????? ?? ??? ???? ?????? ??? ??? ???? 90.91%? 2) ????? ??????? ??? ??? 96.92%? 3) ????? ????? ??? ??? 82.86%? 4) ????? ??????? ??? ??? 97.65%. ????? ??? ???????? ???? ??????? ?? ????? ??????? ??????? ????? ???? ??????? ?? ????? ????? ???????. ??????? ????????: ????? ??????? ?????????? ?????? ????????? ??????? ??????? ??????.